SIMBOL-SIMBOL ISLAM DALAM ARSITEKTUR MASJID TUA ACEH: AKULTURASI DENGAN BUDAYA MARITIM NUSANTARA - Miftahul Jannah; Nurmila (NIHAYAH: Journal of Islamic Studies, 2025)
This article explores the dialectic between Islamic symbols and maritime culture in the architectural design of old mosques in Aceh, serving as a religious expression and local identity among coastal Muslim communities. Mosques in Aceh are not merely places of worship but also visual media that record the historical trajectory of Islamization and cultural acculturation. This study aims to reveal how architectural elements such as pillars made from repurposed ship timber, ornamental motifs of fish and waves, and the orientation of buildings facing the sea or river reflect the fusion between Islamic values and local maritime traditions. A qualitative approach is employed through field observations of several historic mosques, including Baiturrahman and Indrapuri Mosques, combined with semiotic analysis of visual symbols and spatial arrangements.The data are derived from architectural observations and historical documents such as Hikayat Aceh and Bustanussalatin. The findings indicate that dominant Islamic symbols have creatively merged with local elements, transforming the mosque into a “visual text” that conveys the values of tawḥīd, maritime identity, and ecological consciousness. The study also highlights the selective process of Islamization, where non-Islamic symbols such as mythical creatures are excluded, while neutral maritime symbols are absorbed into religious constructions. This research concludes with a call for the preservation and digital documentation of Aceh’s old mosque architecture as an integral part of Islamic Nusantara civilization.